Chronic obstructive pulmonary disease (COPD) and comorbidities - Batura-Gabryel, Halina (Przewodnik Lekarza/Guide for GPs Supplement, 2007)
This paper presents a new definition of chronic obstructive pulmonary disease (COPD) according to GOLD 2006. A new look at COPD emphasises the potential role of comorbidities in the health outcomes of COPD patients, and pathogenic factors (e.g. inflammation) that may link COPD and comorbid conditions. COPD is associated with many comorbidities, particulary those related to cardiovascular-, bone-, and other smoking related conditions.